2019
DOI: 10.1002/iju5.12122
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of inappropriate antidiuretic hormone secretion as a side effect of chemotherapy for testicular cancer: A case report

Abstract: Introduction Inappropriate antidiuretic hormone secretion syndrome can be a serious adverse event of cisplatin‐based chemotherapy. Cisplatin had to be changed to other drugs or chemotherapy completely discontinued in earlier reported cases. Case presentation Three cycles of bleomycin, etoposide, and cisplatin chemotherapy were planned for a 40‐year‐old man with a diagnosis of lymph node recurrence of testicular cancer. On day 9, he suffered from vomiting and mental disturbance. Severe hyponatremia (110 mEq/L) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Malignancy can be associated with hyponatremia due to poor diet, adrenal dysfunction, renal or cerebral salt wasting, and SIADH via ectopic arginine vasopressin (AVP) production or chemotherapy-induced AVP stimulation. 10 Further, paraneoplastic syndrome is a crucial aspect to consider. The tumors most commonly resulting in hyponatremia of the SIADH type are lung, breast, and head and neck tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Malignancy can be associated with hyponatremia due to poor diet, adrenal dysfunction, renal or cerebral salt wasting, and SIADH via ectopic arginine vasopressin (AVP) production or chemotherapy-induced AVP stimulation. 10 Further, paraneoplastic syndrome is a crucial aspect to consider. The tumors most commonly resulting in hyponatremia of the SIADH type are lung, breast, and head and neck tumors.…”
Section: Discussionmentioning
confidence: 99%
“…3 In previously reported cases of cisplatin-related SIADH, cisplatin has been replaced with another drug or chemotherapy has been discontinued; Maeda et al, however, continued to administer BEP chemotherapy and successfully treated this patient. 3 They demonstrated that the threat of SIADH as a severe adverse event can be overcome through the careful monitoring of sodium levels and appropriate mineral recruitment. 3 I would like to send a message to readers as well as to the authors.…”
mentioning
confidence: 97%
“…3 They demonstrated that the threat of SIADH as a severe adverse event can be overcome through the careful monitoring of sodium levels and appropriate mineral recruitment. 3 I would like to send a message to readers as well as to the authors. Although the BEP regimen is the gold standard for induction chemotherapy in patients with metastatic GCC, we need not persist with the BEP regimen when complications arise.…”
mentioning
confidence: 99%
See 2 more Smart Citations